PENGARUH PERBEDAAN ANTARA LABA AKUNTANSI DAN LABA FISKAL TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia) - Pungki Arfiyanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The focus of this study is to see the relationship between accounting earnings and fiscal earnings with earnings persistence. I also examine earnings persistence using book-tax differences betwen accounting earnings and fiscal earnings, I tested whether positive book-tax differences and negative book-tax differences can be used to measure earnings persistence. I find that companies with positive book-tax differences and negative book-tax differences have significantly less persistence earnings. Therefore this research finds that book-tax income differences has the ability to detect earnings quality, which is the persistence of future earnings. This study also analyzed the role of book-tax differences in indicating the persistence of earning one period ahead in manufacturer company that listing in Indonesian Stock Excange ( IDX) since 2008 until 2010. Data that used in this research is financial statements from each company, publized through website www.idx.co.id. Analysis method that used in this research is quantitative method with multiple regression. Sampling method that used is purposive sampling. Variables that used in this research are earning before income tax one periode ahead as Y and earnings before tax at this period.as X. This research also using book-tax differences as moderating variable.The results of this study concluded that positive book-tax differences have negative significant toward to earning before income tax one period ahead. It showed that firms with large positive book-tax differences have earnings that are less persistent than firms with negative book-tax differences.Keyword: persistence of earning, earning before tax one periode ahead, multiple regression, moderating variable, Book-tax difference, deferred tax expense.